2001
DOI: 10.1103/physrevlett.86.3985
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Measurement of theB7e(p,γ)B

Abstract: We have measured the cross section of the 7Be(p,gamma)8B reaction for E(c.m.) = 185.8, 134.7, and 111.7 keV using a radioactive 7Be target (132 mCi). Single and coincidence spectra of beta+ and alpha particles from 8B and 8Be* decay, respectively, were measured using a large acceptance spectrometer. The zero energy S factor inferred from these data is 18.5+/-2.4 eV b and a weighted mean value of 18.8+/-1.7 eV b (theoretical uncertainty included) is deduced when combining this value with our previous results at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 26 publications
10
90
0
Order By: Relevance
“…The recent 7 Be(p, γ) measurements yield values of S 17 (0) which are clustered around 18.5 eV b [5] and 22.0 eV b [6]. Our S 17 (0) (22.0 eV barn) is closer to two latest direct capture measurement results which claim good accuracy.…”
Section: Valence Proton Radius In 8 B and Astrophysical S 17 Factorsupporting
confidence: 64%
See 1 more Smart Citation
“…The recent 7 Be(p, γ) measurements yield values of S 17 (0) which are clustered around 18.5 eV b [5] and 22.0 eV b [6]. Our S 17 (0) (22.0 eV barn) is closer to two latest direct capture measurement results which claim good accuracy.…”
Section: Valence Proton Radius In 8 B and Astrophysical S 17 Factorsupporting
confidence: 64%
“…(number to be inserted here) c 2017 The Institute of Physics S 17 (0)] is determined either by direct measurements [5,6] or by indirect methods such as Coulomb dissociation [7] and transfer reactions [8,9]. Efforts have also been made to calculate the cross section of this reaction within the framework of the shell model and the cluster model [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the latter has been redetermined by new high-precision direct measurements [4,5,6,7] and extrapolated to zero energy with the help of a theoretical model [8]. The resulting zero-energy astrophysical S factors, S 17 (0), however, do not always agree within their quoted errors: Hammache et al [4] found S 17 (0) = 18.8 ± 1.7 eV b, in agreement with other direct-capture data [5,9,10]. In contrast, Junghans et al [6] report a considerably larger value, S 17 (0) = 22.3 ± 0.7 ± 0.5 eV b.…”
mentioning
confidence: 99%
“…The bottom panel (b) compares our data to those of the 7 Be(p,γ) 8 B measurements where the authors have subtracted the contribution from the M1 resonance (Refs. [4,6,7]). At low energies the (p,γ) data of Refs.…”
mentioning
confidence: 99%
“…[10]. Concerning S 17 , we quote an uncertainty of 9%, taking into account the most recent measurements [11].…”
Section: Power Lawsmentioning
confidence: 99%